PEMBELAJARAN KOOPERATIF BERBANTUAN MEDIA GAMBAR UNTUK MENINGKATKAN KEMAMPUAN BERCERITA SISWA - Eni Umaryati (FKIP ULM, 2020)
Abstract. The relatively low storytelling skills of students encourages researcher to propose alternative solution to solve the problem in the form of using picture-assisted cooperative models. This classroom action research is conducted at class VIIIA students of SMPN 6 Banjarmasin. Data collection techniques were carried out through observation using observation sheets and student response questionnaires, and test techniques using descriptive questions. The results showed that students’ activity in learning increased from 44% in cycle I to 89% in cycle II. The students’ learning outcomes also increased from 65% in cycle I to 89% in cycle II. Students also gave positive responses to learning process by 90%. It can be concluded that picture-assisted cooperative models is effective in improving students' storytelling skills.Keywords: storytelling skills, cooperative learning model, picturesAbstrak. Kemampuan bercerita siswa yang relatif masih rendah mendorong peneliti untuk mengajukan alternatif solusi pemecahan masalah berupa penggunaan model kooperatif berbantuan media gambar. Penelitian Tindakan kelas ini ditujukan kepada siswa kelas VIIIA SMPN 6 Banjarmasin. Teknik pengumpulan data dilakukan melalui observasi menggunakan lembar pengamatan dan angket respon siswa, serta teknik tes menggunakan soal uraian. Hasil penelitian menunjukkan bahwa aktivitas siswa dalam pembelajaran mengalami peningkatan dari 44% pada siklus I menjadi 89% pada siklus II. Hasil belajar siswa juga mengalami peningkatan dari 65% pada siklus I menjadi 89% pada siklus II. Siswa juga memberikan respon positif terhadap pembelajaran sebesar 90%. Disimpulkan bahwa pembelajaran kooperatif berbantuan media gambar efektif meningkatkan kemampuan bercerita siswa. Kata Kunci: kemampuan bercerita, model pembelajaran kooperatif, media gambar